2020
DOI: 10.1007/s11120-020-00750-x
|View full text |Cite
|
Sign up to set email alerts
|

From δ-aminolevulinic acid to chlorophylls and every step in between: in memory of Constantin (Tino) A. Rebeiz, 1936–2019

Abstract: Constantin A. (Tino) Rebeiz, a pioneer in the field of chlorophyll biosynthesis, and a longtime member of the University of Illinois community of plant biologists, passed away on July 25, 2019. He came to the USA at a time that was difficult for members of minority groups to be in academia. However, his passion for the complexity of the biochemical origin of chlorophylls drove a career in basic sciences which extended into applied areas of environmentally friendly pesticides and treatment for skin cancer. He w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Further, they led Maarib to prove that indeed plants have both monovinyl and divinyl Chl a, i.e., there are indeed different Chls a in vivo! Maarib's discovery of divinyl Chl a continued to be of interest to researchers around the world; see e.g., Goericke and Repeta (1992) We note that even before Maarib had proved the different chemical nature of the Chls, differences in spectra were known (see Govindjee et al 2020, for references to papers from Tino Rebeiz's research group). Further, Freyssinet et al (1980) showed that different amounts of spectral forms (suggested to be divinyl Chls) were present in different subchloroplast fractions.…”
Section: The New Chlorophyll: Research At Cambridge Ukmentioning
confidence: 98%
See 3 more Smart Citations
“…Further, they led Maarib to prove that indeed plants have both monovinyl and divinyl Chl a, i.e., there are indeed different Chls a in vivo! Maarib's discovery of divinyl Chl a continued to be of interest to researchers around the world; see e.g., Goericke and Repeta (1992) We note that even before Maarib had proved the different chemical nature of the Chls, differences in spectra were known (see Govindjee et al 2020, for references to papers from Tino Rebeiz's research group). Further, Freyssinet et al (1980) showed that different amounts of spectral forms (suggested to be divinyl Chls) were present in different subchloroplast fractions.…”
Section: The New Chlorophyll: Research At Cambridge Ukmentioning
confidence: 98%
“…According to her healthcare providers, she was courageous until the end and died peacefully. Maarib leaves behind two wonderful Pickett andAckerly 2008 andGrubb 2008; and for Tino Rebeiz, see Govindjee et al 2020) children-who carry the torch of the Bazzaz family. A daughter Sahar, a PhD from Harvard University, is a Professor of History and Middle Eastern Studies, https://www.…”
Section: Epilogmentioning
confidence: 99%
See 2 more Smart Citations
“…In May 2005, Constantin (Tino) Rebeiz (1936Rebeiz ( -2019, well-known for his excellent research on chlorophyll biosynthesis (Rebeiz 2013, Govindjee et al 2020a, organized together with colleagues the 'International Symposium on Chloroplast Engineering' in Urbana-Champaign, Illinois. In this symposium, I was involved as co-organizer being responsible for and leading the session on isoprenoid lipids and the new plastidic DOXP/MEP isoprenoid biosynthesis pathway detected by my group (see , Lichtenthaler 1999.…”
Section: Contacts During the Symposium On Chloroplast Bioengineeringmentioning
confidence: 99%